المحدث عبد الحق الدهلوي وجهوده في خدمة الحديث النبوي الشريف =The Mohaddith Abdul Haq Dahlawi and his efforts in the service of the Prophet’s hadith - Al-Nadwi, Fariduddin Fahimuddin; Mohammed Yaqub, Mohammed Abullais Shamsuddin (Refaad Center for Studies and Research, 2020)
يحتل الشيخ المحدث عبد الحق الدهلوي-صاحب كتاب "لمعات التنقيح في شرح مشكاة المصابيح"- مكانة خاصة في نشر علم الحديث الشريف وعلومه في التاريخ الديني الإسلامي والعلمي للهند الإسلامية في القرن العاشر للهجرة، بعد ما أروى غلته العلمية ونهل المنهل العلمي العذب من علماء الحرمين الشريفين عاد إلى الهند بأمر من شيخه الشيخ عبد الوهاب المتقي عودةً بمنزلة ثورة علمية ونهضة حديثية، وقام بتجديد العلوم وشرحها من خلال التدريس والتأليف والتصنيف، وكان لـ"علم الحديث" الحظ الأوفر والقدر الأكبر من عنايته بين تلك العلوم، ولعل هو أول من وضع لبنة علم الحديث الشريف في شمال الهند وخاصة بدار الملك (دهلي) عاصمة الهند وأطرافها في ذلك الزمن، ونشر العلوم، لاسيما الحديث الشريف وعلومه حيث تيسّر له ما لم يتيسر مثلُه لأحد من العلماء السابقين في ديار الهند، وظلت مدرسته للحديث الشريف في دهلي مهداً للعلوم والفنون، ومركزاً لنشر الحديث الشريف وعلومه أكثر من نصف قرن على نطاق واسع. إن الهدف من هذا البحث المتواضع هو دراسة أبرز جوانب حياة المحدث الدهلوي ومآثره في الحديث الشريف، لذلك يركّز الباحث في بحثه هذا على التعريف بأبرز جوانب حياة المحدث الدهلوي، مع التعريف بمؤلفاته في الحديث النبوي الشريف متناً وشرحاً من خلال المنهج الوصفي والاستقرائي. ********************************************************** Undoubtedly, the Indian scholar, the authority in Hadith, the author of several books such as ´Ashe‘aah al-Lam‘aÉt (in Persian language) and Lam‘aÉt al-Tanqeeh (in Arabic language) Sheikh ‘Abd al-Haqq al-Dehlawi, which he wrote after he returned back from Hijaz and settled down in India, he served the knowledge and popularized it, especially the noble Hadith and its sciences, as no one from the previous scholars in India was able to do the same. He started scholarly explanation on a famous Hadith book al-MishkÉt in Persian language at the beginning, later he felt that some words and terminologies needed to be expressed in Arabic language, so he decided to rewrite the book in Arabic, in addition to writing it in Persian separately. His books are fine witness on his wide knowledge of the contents of Hadith and its commentaries. The truth is that he dedicated himself in teaching Hadith books, issuing legal opinions to people, writing, explaining and translating the books till they were accepted by Allah (SWT) and then the scholars. He was among the scholars who spread the noble Hadith and its sciences in the Indian subcontinent widely .